Influence of Soil Physicochemical Properties and Microbial Dynamics on Incidence of Major Diseases of Tomato in High Production Regions of Himachal Pradesh - Bhardwaj, Swadha; Chandel, Sunita; Jandaik, Savita; Kumar, Pradeep; Devi, Sunita (International Journal of Economic Plants, 2025)
The study was conducted from March to September, 2021–2022 in the Solan and Sirmour districts of Himachal Pradeshwith an aim to assess the influence of soil physicochemical characteristics and microbial communities on the incidence of major tomato diseases in high-production areas of Himachal Pradesh. Soil samples were collected from tomato-growing fields across multiple locations and analyzed for pH, electrical conductivity, organic carbon, and nutrient content. Standard protocols were followed for physicochemical analyses, and microbial populations were quantified using serial dilution and plating methods. Damping-off incidence ranged from 21.33% to 51.00%, while wilt incidence varied between 18.00% to 37.00%. This reflected a high disease pressure influenced by local soil and environmental conditions. Microbial analysis revealed spatial variation. Panwa recorded the highest fungal count (75×10³ cfu g-1 soil), while Kandaghat recorded the highest bacterial count (98×10⁶ cfu g-1 soil), highlighting heterogeneity in microbial distribution. Soil pH varied across sites, with slightly alkaline in Palashala and Kurgal. A strong positive correlations were observed between soil pH and microbial counts. Moderate positive correlations were found between, nitrogen, phosphorus, and potassium content with microbial populations. These findings demonstrated that variations in soil physicochemical properties directly influenced microbial dynamics and disease incidences. The results highlighted that soil conditions significantly impact microbial dynamics and disease incidence, emphasizing the need of effective soil health management for sustainable tomato cultivation.